BET bromodomains as novel epigenetic targets for brain health and disease. (15th December 2020) - Singh, Mandakini B.; Sartor, Gregory C.
Abstract: Epigenetic pharmacotherapy for CNS-related diseases is a burgeoning area of research. In particular, members of the bromodomain and extra-terminal domain (BET) family of proteins have emerged as intriguing therapeutic targets due to their putative involvement in an array of brain diseases. With their ability to bind to acetylated histones and act as a scaffold for chromatin modifying complexes, BET proteins were originally thought of as passive epigenetic 'reader' proteins. However, new research depicts a more complex reality where BET proteins act as key nodes in lineage-specific and signal-dependent transcriptional mechanisms to influence disease-relevant functions. Amid a recent wave of drug development efforts from basic scientists and pharmaceutical companies, BET inhibitors are currently being studied in several CNS-related disease models, but safety and tolerability remain a concern. Here we review the progress in understanding the neurobiological mechanisms of BET proteins and the therapeutic potential of targeting BET proteins for brain health and disease. Highlights: BET proteins have emerged as an integral component of gene regulatory networks associated with brain health and disease. With the recent development of selective inhibitors, many opportunities exist for targeting BET proteins in brain diseases.